Language development in bimodal bilingual autistic children: a case series of hearing children with deaf signing parents - Shield, Aaron (Frontiers in Language Sciences, 2025)
IntroductionIt is often assumed that sign language may be a more accessible alternative to speech for autistic children who have minimally expressive spoken language. However, this hypothesis remains largely untested in children exposed to both modalities from birth. This case series describes the developmental, cognitive, and language profiles of seven hearing autistic children of Deaf parents (CODAs) with native exposure to American Sign Language (ASL) and English.MethodsStandardized assessments of receptive language, nonverbal cognition, and autism characteristics were collected alongside observational and parent-report data.ResultsResults revealed substantial individual variation: some children showed delays in both ASL and English; others showed slightly better ASL comprehension; and still others were clearly dominant in English, despite early access to ASL. Notably, no child demonstrated a consistent sign-language advantage.DiscussionThese findings challenge the assumption that sign is inherently more accessible to autistic children and highlight the need for individualized, modality-sensitive assessment. This study provides the first in-depth look at bimodal bilingualism in autism, offering a novel perspective on bilingual language acquisition in autism.